Penta-Helix Collaboration In The Commodification Of Balinese Traditional Dance As A Tourism Attraction Post Covid-19 Pandemic In Gianyar - Putu Herny Susanti; I Made Sudarsana; I Wayan Eka Sudarmawan (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to examine the Penta-Helix Collaboration in the commodification of Balinese traditional dance as a Post-Covid-19 Pandemic Tourist Attraction in Gianyar. Apart from having cultural arts appeal, the hospitality of the residents also supports the uniqueness of Balinese cultural tourism. Cultural arts and living habits of the Balinese people are the essence of cultural tourism. Along with the development of tourism in Bali, traditional Balinese dance has experienced commodification. This research is a qualitative descriptive research, so that all understanding, explanations and findings will be described in the form of descriptions of sentences as a result of argumentative critical interpretation based on research data. The commodification of Barong Performing Arts in several areas in Bali, especially Batubulan Village, Gianyar, is understood, explained.